2023
DOI: 10.3390/ijms24065181
|View full text |Cite
|
Sign up to set email alerts
|

The Tissue Response to Hypoxia: How Therapeutic Carbon Dioxide Moves the Response toward Homeostasis and Away from Instability

Abstract: Sustained tissue hypoxia is associated with many pathophysiological conditions, including chronic inflammation, chronic wounds, slow-healing fractures, microvascular complications of diabetes, and metastatic spread of tumors. This extended deficiency of oxygen (O2) in the tissue sets creates a microenvironment that supports inflammation and initiates cell survival paradigms. Elevating tissue carbon dioxide levels (CO2) pushes the tissue environment toward “thrive mode,” bringing increased blood flow, added O2,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 102 publications
0
1
0
Order By: Relevance
“…Such beneficial effects of balneotherapy are considered to be due to marked vasodilatory and anti-inflammatory actions of CO 2 . In fact, both clinical and experimental investigations have revealed that CO 2 therapy improves blood flow in the ischemic limb in PAD [4,[19][20][21][22][23][24][25][26][27][28]. Due to the microcirculation promoting effect of CO 2 , angiography using CO 2 has been employed to monitor immediate response to endovascular therapy of PAD [29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…Such beneficial effects of balneotherapy are considered to be due to marked vasodilatory and anti-inflammatory actions of CO 2 . In fact, both clinical and experimental investigations have revealed that CO 2 therapy improves blood flow in the ischemic limb in PAD [4,[19][20][21][22][23][24][25][26][27][28]. Due to the microcirculation promoting effect of CO 2 , angiography using CO 2 has been employed to monitor immediate response to endovascular therapy of PAD [29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%